Investigation of the elemental partitioning behaviour and site preference in ternary model nickel-based superalloys by atom probe tomography and first-principles calculations. Issue 21 (22nd July 2016) - Liu, S. H.; Liu, C. P.; Liu, W. Q.; Zhang, X. N.; Yan, P.; Wang, C. Y.
Abstract : The topologically close-packed phase formation is heavily influenced by the concentrations of Co, Ru, and Cr in Ni-based superaloys. For this purpose, we investigate the partitioning behaviour and site preference of these additions in the model Ni–Al–X single crystal superalloys by atom probe tomography and first-principles calculations. Compared with the commercial multicomponent superalloys, Co and Ru still strongly partition to the phase, while Cr weakly partitions to the phase in the ternary model alloys. Based on the phase composition analyses, Ru and Cr atoms preferentially substitute for the Al sublattice sites, whereas Co atoms substitute at both Al and Ni sublattice sites in the ordered - phase. First-principles calculations on the substitutional formation energies at 0 K were performed to understand the site preference, and the partitioning coefficient of additions was given in a quantitative model. The partitioning behaviour and site preference of Co, Ru, and Cr by theoretical calculations are consistent with the experimental results.